Variation in femoral length across different age groups and its correlation with walking patterns: A cross-sectional observational study. - Dr. K. Zia Ul Haq; Kotra, Dr. Siva Kumar; Dr. Sowmyashree U (Student’s Journal of Health Research Africa, 2025)
Background: Femoral length plays a vital role in determining lower limb biomechanics and walking efficiency. Variations in femoral length across different age groups may influence gait parameters such as step length and walking speed. This study aimed to investigate femoral length variations with age and examine their correlation with walking patterns. Methods: A cross-sectional observational study was conducted on 50 participants, divided into five equal age groups: 10–19, 20–29, 30–39, 40–49, and ≥50 years. Femoral length was measured using standardized anthropometric techniques. Gait parameters, including step length and walking speed, were recorded using a motion analysis setup. Descriptive statistics, ANOVA, and Pearson correlation analysis were employed to analyze the data. Results: The mean femoral length was highest in the 20–29 age group (45.1 ± 2.1 cm) and lowest in the 10–19 group (41.8 ± 2.4 cm). Walking parameters showed similar trends, with peak step length (72.4 ± 4.8 cm) and walking speed (1.51 ± 0.14 m/s) observed in the 20–29 group. A moderate positive correlation was found between femoral length and step length (r = 0.62, p < 0.001), as well as between femoral length and walking speed (r = 0.58, p < 0.001). Conclusion: Femoral length significantly varies across age groups and is positively correlated with walking efficiency. These findings underscore the importance of femoral length in gait biomechanics and may have implications in orthopedic assessment, rehabilitation, and prosthetic design. Recommendations: Incorporate femoral length assessment in gait evaluations to optimize rehabilitation strategies, prosthetic fitting, and age-specific orthopedic interventions.